Integration, Geography and the Burden of History - Gianmarco Ottaviano (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
This paper develops a simple two-region two-sector general equilibrium model of trade and migration where one monopolistically competitive sector generates local pecuniary externalities. The aim is to gain insight on the question whether economic integration can be expected to increase the differences in industrial structure between more and less developed regions. It is shown that a reduction in trade and/or migration costs weakens the lock-in effect of historical events while strengthening the role of expectations.
Keywords: 330